Severity assessment of burned skin based on anisotropy of optical coherence elastography - Heng Liu; Di Yang; Renfei Jia; Weike Wang; Lili Shao; Quanzhong Liu; Yanmei Liang (Journal of Innovative Optical Health Sciences)
Distinguishing the severity of burned skin from structural optical coherence tomography (OCT) intensity maps remains a challenging task, and functional imaging from an elastic perspective can improve the accuracy of burned skin examination. As a functional extension of OCT, optical coherence elastography (OCE) can reveal the mechanical properties of samples while inheriting the imaging advantages of OCT. In this study, we used OCE to reveal the shear modulus and anisotropy parameters of burned skin before and after burning. A porcine skin burn model was constructed at a series of burned time durations and tested by elastic anisotropy imaging. Normal skin after hydration maintains good consistency in shear modulus. Interestingly, the shear modulus and longitudinal modulus of the burned skin show a tendency to stepwise increase with increasing burned times. A dataset was constructed by sampling the modulus parameters of burned skin maps through a scratch window, and its category was automatically identified by K-means and density peak clustering (DPC) algorithms with good agreement. The elastic anisotropy-based skin burn assessment method shows a prospect to be supplemented into the nondestructive means of burned skin examination.